2009
DOI: 10.1097/prs.0b013e3181a3f3ae
|View full text |Cite
|
Sign up to set email alerts
|

An Anatomical Study of External Carotid Artery Vascular Territories in Face and Midface Flaps for Transplantation

Abstract: Dual soft-tissue perfusion was confirmed in most specimens at the nasal, central face, and maxilla. The inclusion of the maxilla in the design of a facial composite allotransplant demands bilateral vascular pedicles based on the internal maxillary arteries. The authors highlight a procurement strategy for design of such flaps.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
0
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(33 citation statements)
references
References 31 publications
(33 reference statements)
1
31
0
1
Order By: Relevance
“…The maxillary artery is considered the main artery of the maxilla and the removal of these two components is considered a reliable, successful graft. 3,4 However, the artery is located deep within the tissue and is difficult to access. Instead, dissection and removal of the facial artery would be quicker and easier than the maxillary artery and could provide a valuable alternative for facial allotransplantations.…”
Section: Introductionmentioning
confidence: 99%
“…The maxillary artery is considered the main artery of the maxilla and the removal of these two components is considered a reliable, successful graft. 3,4 However, the artery is located deep within the tissue and is difficult to access. Instead, dissection and removal of the facial artery would be quicker and easier than the maxillary artery and could provide a valuable alternative for facial allotransplantations.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous prior anatomical studies have been reported in the literature of potential transplant options for osteocutaneous transfer involving the use of the external carotid system with the internal maxillary vessels as the primary blood supply to the palate. [5][6][7][8][9][10] While the anterior wall of the maxilla can be vascularized based on the periosteal supply from the overlying soft tissue, which is supplied by the facial arterial system, the potential of the facial arterial system supplying the potential watershed area of the posterior hard palate had not previously been considered. The question remained of how much blood supply this region would get from mucosal arcades from the buccal mucosa intraorally and from Kiesselbach plexus communications to the posterior nasal vessels from the anterior nasal cavity.…”
Section: Anatomical Design and Flap Preparationmentioning
confidence: 99%
“…9,17 However, there is accumulating evidence that the facial artery can adequately perfuse both the entire maxilla and the mandible anteriorly from the insertion of the masseter muscle. 37,38 A successful, defined by improved esthetic and functional outcome after surgery, facial transplantation suggests that the facial artery alone can perfuse a midfacial allograft that includes the maxilla.…”
Section: ) Can the Facial Artery Alone Perfuse The Maxilla?mentioning
confidence: 99%
“…16 This concept suggests that multiple arteries are needed for perfusion of the facial skin and most of the facial skin is supplied by the superficial temporal, facial, and ophthalmic arteries. 16 However, several anastomotic networks allow perfusion of multiple adjacent territories [17][18][19][20] or across the midline. 8,9 Thus, a source artery can also perfuse neighboring angiosomes when connecting potential vessels, called "choke vessels," open, and subsequently develop into collateral vessels.…”
Section: Donor Vessels and Angiosomesmentioning
confidence: 99%
See 1 more Smart Citation